2013
DOI: 10.4317/jced.51113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recycling and bonding agent application on bond strength of stainless steel orthodontic brackets

Abstract: Objectives: 1) to assess different methods of recycling orthodontic brackets, 2) to evaluate Shear Bond Strength (SBS) of (a) new, (b) recycled and (c) repeated recycled stainless steel brackets (i) with and (ii) without bracket base primer. Study Design: A total of 180 extracted human premolar teeth and 180 premolar stainless steel brackets were used. One hundred teeth and 100 brackets were divided into five groups of 20-teeth each. Four methods of recycling orthodontic brackets were used in each of the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Buchman [29] stated that when the stainless steel bracket is subjected to high temperature, chromium carbide precipitate is formed leading to general weakening of the structure. Accordingly aming for 5 seconds was used by Bansal et al [13], Bahnasi et al [10], Chetan et al [8]. So, in this study, aming was done for 5 seconds then quenched in water at room temperature and dried in an air stream.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buchman [29] stated that when the stainless steel bracket is subjected to high temperature, chromium carbide precipitate is formed leading to general weakening of the structure. Accordingly aming for 5 seconds was used by Bansal et al [13], Bahnasi et al [10], Chetan et al [8]. So, in this study, aming was done for 5 seconds then quenched in water at room temperature and dried in an air stream.…”
Section: Discussionmentioning
confidence: 99%
“…Group I : Control (new brackets, assigned with "C") Group II : Flaming group (assigned with "F") Group III : Flaming with sandblasting group (assigned with "S") Group IV : Flaming with ultrasonic cleaning group (assigned with "U") Before bonding, the buccal surfaces of the teeth were cleaned with ne pumice powder in water using a cup [7,8,10]. The buccal surface of each tooth was etched for 30 seconds with 37% phosphoric acid gel [18][19][20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before bonding, the buccal surfaces of the teeth were cleaned with fine pumice powder (DPI, New Delhi, India) in water using a cup [ 4 , 5 , 8 ]. The buccal surface of each tooth was etched for 30 seconds with 37% phosphoric acid gel (Ormco corp., Orange, CA, USA) [ 16 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Brackets should not be adversely affected after recycling with different methods. Previous studies have reported that recycling with flaming results in shear bond strength below the recommended range of clinical need [ 4 , 5 , 7 , 8 ], while recycling with sandblasting gives clinically acceptable shear bond strength [ 4 , 8 13 ]. SBS of brackets recycled by flaming with sandblasting was reported much less in a study by Gupta et al (2.05 MPa) [ 10 ], and the large value (26.94 MPa) was reported in a study by Bansal and Bansal [ 11 ].…”
Section: Introductionmentioning
confidence: 99%